Genetic analysis of resistance to bean leaf crumple virus identifies a candidate LRR‐RLK gene. (22nd February 2023) - Ariza‐Suarez, Daniel; Keller, Beat; Spescha, Anna; Aparicio, Johan Steven; Mayor, Victor; Portilla‐Benavides, Ana Elizabeth; Buendia, Hector Fabio; Bueno, Juan Miguel; Studer, Bruno; Raatz, Bodo
SUMMARY: Bean leaf crumple virus (BLCrV) is a novel begomovirus (family Geminiviridae, genus Begomovirus ) infecting common bean ( Phaseolus vulgaris L.), threatening bean production in Latin America. Genetic resistance is required to ensure yield stability and reduce the use of insecticides, yet the available resistance sources are limited. In this study, three common bean populations containing a total of 558 genotypes were evaluated in different yield and BLCrV resistance trials under natural infection in the field. A genome‐wide association study identified the locus BLC7.1 on chromosome Pv07 at 3.31 Mbp, explaining 8 to 16% of the phenotypic variation for BLCrV resistance. In comparison, whole‐genome regression models explained 51 to 78% of the variation and identified the same region on Pv07 to confer resistance. The most significantly associated markers were located within the gene model Phvul.007G040400, which encodes a leucine‐rich repeat receptor‐like kinase subfamily III member and is likely to be involved in the innate immune response against the virus. The allelic diversity within this gene revealed five different haplotype groups, one of which was significantly associated with BLCrV resistance. As the same genome region was previously reported to be associated with resistance against other geminiviruses affecting common bean, our study highlights the role of previous breeding efforts for virus resistance in the accumulation of positive alleles against newly emerging viruses. In addition, we provide novel diagnostic single‐nucleotide polymorphism markers for marker‐assisted selection to exploit BLC7.1 for breeding against geminivirus diseases in one of the most important food crops worldwide. Significance Statement: A candidate gene encoding a leucine‐rich repeat receptor‐like kinase (LRR‐RLK) located on chromosome Pv07 was associated with resistance against bean leaf crumple virus (BLCrV), a novel begomovirus affecting common bean production in Colombia and potentially other areas in Latin America.